Study on Education Level and Consequences of Licensing and In-terest in Making Small Business Licensing - Rahayu Mardikaningsih; Samsul Arifin (Journal of Social Science Studies (JOS3), 2021)
This correlation study involves three variables, namely education level, licensing consequences, and interest in making small business licensing because there are still many small-scale entrepreneurs who are reluctant to take care of business licensing even though the government has given it easy. This study involved 29 small businesses in a sub-district in Mojokerto district. The total number of small businesses that have permits is as much as the sample used so that the total sampling method is used. The data collection technique used a questionnaire with a six-scale Likert scale. Test the instrument with validity and reliability which is then tested for normality and linearity as well as hypothesis testing with product moment correlation analysis tools. The finding in this study is that there is a significant relationship between education level and interest in making small business licenses. The relationship between the two variables is quite strong. In addition, it was also found that there is a significant relationship between the consequences of licensing and interest in making small business licensing even though the relationship between the two is weak.